2019
DOI: 10.1155/2019/5407126
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus X Protein-Induced RORγ Expression to Promote the Migration and Proliferation of Hepatocellular Carcinoma

Abstract: Aberrant expression of RORγ is implicated in cancer development. A previous study identified that RORγ functions as a tumor promoter to drive hepatocellular carcinoma (HCC) growth. However, its expression and significance in HCC remain unclear. The central finding of this work is that RORγ was overexpressed in HCC due to its dysfunction of promoter methylation, and hepatitis B virus X protein (HBx) can remarkably induce the expression of RORγ in hepatocellular carcinoma through enhancing the transcriptional fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Huang reported that RORc is highly expressed in liver tumor tissues, and its expression is closely associated with HBV infection, suggesting that RORc is an oncogene involved in the proliferation and migration of hepatocellular carcinoma. 18 Some reports also described RORc overexpression in lung cancer, breast cancer, and melanoma. As a subtype of RORc, RORct was reported to inhibit the development of colon cancer, 36 and RORct expression in colon cancer remains controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Huang reported that RORc is highly expressed in liver tumor tissues, and its expression is closely associated with HBV infection, suggesting that RORc is an oncogene involved in the proliferation and migration of hepatocellular carcinoma. 18 Some reports also described RORc overexpression in lung cancer, breast cancer, and melanoma. As a subtype of RORc, RORct was reported to inhibit the development of colon cancer, 36 and RORct expression in colon cancer remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 However, RORγ was identified as an oncogene in liver cancer, lung cancer, prostate cancer, gastric cancer, cervical cancer, and multiple myeloma. 18 22 Some researchers also indicated that RORγ could exert pro-tumor effects in breast cancer through regulating LC3, 15 , 23 suggesting that the function of RORγ varies among different cancers.…”
Section: Introductionmentioning
confidence: 99%
“…RORγ overexpression is associated with promoter methylation and HBx protein. Furthermore, HBx-induced RORγ may facilitate the proliferation and migration of hepatoma cells[ 93 ], and RORα may be a possible diagnostic and prognostic biomarker for disease severity[ 94 ]. Overexpression of RORα , CRY2 , and PER1 is associated with a better survival of HCC patients, and regulating the circadian rhythm gene may help in the chronotherapy of such patients[ 94 ].…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…Moreover, CLOCK and BMAL1 control transcription of the pattern recognition receptor, which is involved in nucleic acid detection during viral infections[ 104 ]. RORγ regulates the differentiation of Th17 cells, which secrete IL-17, an essential regulator of pro-inflammatory signaling[ 93 ]. REV-ERBα has a protective effect in various inflammatory processes[ 105 ].…”
Section: Circadian Rhythmmentioning
confidence: 99%
“…ROR expression is enhanced in HCC patients with HBV infection and overexpression of ROR in liver cancer cells can enhance their migration and proliferation in vitro (Y. Huang et al, 2019). Thus, we wanted to rule out a possible contribution of knocking out RORc expression in hepatocytes to the phenotype of IKK RORc KO mice.…”
Section: Intrahepatic Cholangiocarcinoma (Icca) Load Is Decreased In ...mentioning
confidence: 99%